A dangerous food binge: a case report of hypokalemic periodic paralysis and review of current literature - Maria Carolina Colucci; Marica Fabiana Triolo; Simona Petrucci; Flaminia Pugnaloni; Massimiliano Corsino; Melania Evangelisti; Maria Cecilia D'Asdia; Giovanni Di Nardo; Matteo Garibaldi; Gianluca Terrin; Pasquale Parisi (BMC, 2022)
Abstract Background Hypokalemic periodic paralysis is a rare neuromuscular genetic disorder due to defect of ion channels and subsequent function impairment. It belongs to a periodic paralyses group including hyperkalemic periodic paralysis (HEKPP), hypokalemic periodic paralysis (HOKPP) and Andersen-Tawil syndrome (ATS). Clinical presentations are mostly characterized by episodes of flaccid generalized weakness with transient hypo- or hyperkalemia. Case presentation A teenage boy presented to Emergency Department (ED) for acute weakness and no story of neurological disease, during the anamnestic interview he revealed that he had a carbohydrates-rich meal the previous evening. Through a focused diagnostic work-up the most frequent and dangerous causes of paralysis were excluded, but low serum potassium concentration and positive family history for periodic paralyses raised the diagnostic suspicion of HOKPP. After the acute management in ED, he was admitted to Pediatric Department where a potassium integration was started and the patient was counselled about avoiding daily life triggers. He was discharged in few days. Unfortunately, he presented again because of a new paralytic attack due to a sugar-rich food binge the previous evening. Again, he was admitted and treated by potassium integration. This time he was strongly made aware of the risks he may face in case of poor adherence to therapy or behavioral rules. Currently, after 15 months, the boy is fine and no new flare-ups are reported. Conclusion HOKPP is a rare disease but symptoms can have a remarkable impact on patients' quality of life and can interfere with employment and educational opportunities. The treatment aims to minimize the paralysis attacks by restoring normal potassium level in order to reduce muscle excitability but it seems clear that a strong education of the patient about identification and avoidance triggering factors is essential to guarantee a benign clinical course. In our work we discuss the typical clinical presentation of these patients focusing on the key points of the diagnosis and on the challenges of therapeutic management especially in adolescence. A brief discussion of the most recent knowledge regarding this clinical condition follows.